Perancangan dan Pembuatan Aplikasi Student Reminder Berbasis Android - Pambudi, Robertus; Purba, Kristo Radion (Jurnal Infra, 2018)
Student Reminder is an android based application. Unlike a reminder in general. And student reminder has a special user that is the student as the main user. Many students have difficulty in managing their college schedule and also the schedule of collecting tasks because of students' ignorance of the schedule of task collection. Most reminder apps need to manually procedure to input user activity schedules because has no feature for perform automatic updates to smartphone google calendar from Petra Christian University database. During this time students still use the manual way to record the schedule by using the agenda book or recorded in the smartphone with the manual. The process of making this application using android studio developer and using java programming language. Android studio is used to create a view on the application, making the function to retrieve data from PHP. And make auto synchronize to google calendar. PHP is used to extract values from a database and display those values in a web view. JSON is used to read data from PHP to java on android. SQL is used to create database tables and their relationships with other tables.From the results of the design and the making of Student Reminder Application can be concluded among others simple applications and easy to use applications, make it easier for students to view the schedule of lectures, and schedule will automatically enter to student’s google calendar smartphones.